Determining brain fitness to fight: Has the time come?. Issue 4 (2nd October 2015) - Seifert, Tad; Bernick, Charles; Jordan, Barry; Alessi, Anthony; Davidson, Jeff; Cantu, Robert; Giza, Christopher; Goodman, Margaret; Benjamin, Johnny
Abstract: Professional boxing is associated with a risk of chronic neurological injury, with up to 20–50% of former boxers exhibiting symptoms of chronic brain injury. Chronic traumatic brain injury encompasses a spectrum of disorders that are associated with long-term consequences of brain injury and remains the most difficult safety challenge in modern-day boxing. Despite these concerns, traditional guidelines used for return to sport participation after concussion are inconsistently applied in boxing. Furthermore, few athletic commissions require either formal consultation with a neurological specialist (i.e. neurologist, neurosurgeon, or neuropsychologist) or formal neuropsychological testing prior to return to fight. In order to protect the health of boxers and maintain the long-term viability of a sport associated with exposure to repetitive head trauma, we propose a set of specific requirements for brain safety that all state athletic commissions would implement.